Safety Assessment Method for Prefabricated Timber Roof Truss - Salleh Baharudin, Khairul; Bin Ayob, Mohamad; Mohammed Ali Al-Shami, Aiman; Ahmad, Rosnani; Ahmad, Zakiah (International Journal of Engineering and Technology, 2019)
Safety Assessment Method (SAM) is the mechanism used to evaluate the robustness of a structure under the event of local failure such that a progressive collapse may occurs. In this method, the sensitive and key elements are identified to ascertain the structural members that are sensitive to failure and the members that are prime to prevent the subsequent failure of the structure. The sensitive element indicates the first element to induce further progressive failure of the structure while the key element signifies the prime member of the truss that can withstand the progressive load after which a member fail. In this study, a linear static analysis of a truss structure is conducted and the sensitive and key elements are identified. Internal member forces of the truss from seven (7) cases of member failure are computed to determine the robustness of the structure. Subsequently the key and sensitive elements were computed from the result of internal member forces. A prefabricated timber roof truss of Howe configuration was used in the data analysis. The truss resistance and robustness to avoid the progressive collapse are evaluated. Results show that member 2 of the bottom chord is the major key element and member 6 of the bottom chord is the most sensitive element. However, majority of the truss members are of equally importance in the key element and sensitivity index since there is no significant differences are detected.Â Â Â